Flow over a Rotationally-Oscillation Circular Cylinder and Around Two Cylinder Side by Side with Different Movements - Silva , Alice Rosa da; Lázaro , Bruno de Oliveira (Fundamental Research and Application of Physical Science Vol. 8, 2023)
This work has two main objectives: the analysis of the flow dynamics, as well as the behavior of the drag coefficient, around a circular cylinder with rotationally-oscillation. And, the study of the influence of different movements, of two side by side cylinders, on the drag and pressure coefficients. First, a wide range of forcing frequencies, fr , and three values of oscillation amplitudes, A, are considered to analyze the flow dynamics by the vorticity contours. It is important to point out those others investigators for rotationally oscillating case did not capture the 2C mode of vortex shedding, observed in the present study. Second, relevant parameters of the flow around two circular cylinders arranged side by side, with four combinations of alternating motions are presented. All cases are performed for Re =1000, amplitude of oscillation (A) equal to 3, frequency ratio (fr) of 0.5, specific rotation (\(α\)) equal to 0.5 and different values of spacing ratio (L/D). The combination of the type of movement, together with the position of one cylinder in relation to the other, exerts significant influence on the pressure distribution around the cylinder surface and on the average values of the drag coefficient. The smallest value of the average pressure coefficient (Cp =- 3.3), is obtained for the oscillating cylinder when placed side by side with the clockwise rotation cylinder, case 3 and L / D = 1.5. On the other hand, the lowest mean drag coefficient (Cd = 1.0788), is obtained for the cylinder with counterclockwise rotation, located in the lower position in relation to oscillating cylinder in the upper position, with spacing between them of 1.5. Furthermore, the rotation movement is more effective in reducing drag than the rotation-oscillation movement, for the studied frequency ratio.